2003
DOI: 10.1677/joe.0.1760163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lepidium meyenii (Maca), a root with aphrodisiac and fertility-enhancing properties, on serum reproductive hormone levels in adult healthy men

Abstract: Lepidium meyenii (Maca) is a Peruvian hypocotyl that grows exclusively between 4000 and 4500 m in the central Andes. Maca is traditionally employed in the Andean region for its supposed aphrodisiac and/or fertilityenhancing properties.This study was a 12-week double-blind, placebocontrolled, randomized, parallel trial in which active treatment with different doses of Maca Gelatinizada was compared with a placebo. The study aimed to test the hypothesis that Maca has no effect on serum reproductive hormone level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
100
1
16

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(125 citation statements)
references
References 25 publications
5
100
1
16
Order By: Relevance
“…This has also been observed in men treated with 1500 or 3000 mg/ day (Gonzales et al 2003). This suggests that the effect of Maca on spermatogenesis, particularly on stages VIII and IX-XI, could be due to a direct effect on the testis.…”
Section: Figuresupporting
confidence: 53%
“…This has also been observed in men treated with 1500 or 3000 mg/ day (Gonzales et al 2003). This suggests that the effect of Maca on spermatogenesis, particularly on stages VIII and IX-XI, could be due to a direct effect on the testis.…”
Section: Figuresupporting
confidence: 53%
“…Maca, like ginger, is a powerful adaptogene, which improves the body ability to adapt to complicated and stressful situations. Scientific studies have shown that Maca improves memory and neurotransmitter function, increases the amount of oxygen in the blood and enhances libido [5][6][7][8]. Maca alkaloids positively effect hypothalamus and adrenal glands, and this provides energy, and increases vitality [7; 9].…”
Section: Introductionmentioning
confidence: 99%
“…W innym randomizowanym badaniu przeprowadzonym wśród 65 osób chorujących na cukrzycę typu drugiego również wykazano zmniejszenie poziomu glikemii (10%), a nie wykazano wpływu na profil lipidowy. W badaniu Vanschoonbeeka et al [47], w którym podawano cynamon w dawce 1,5 g/dzień przez 6 tygodni grupie 25 kobiet po menopauzie chorym na cukrzycę typu 2 nie zaobserwowano wpływu na stężenie glukozy we krwi, wrażliwość na insulinę oraz profil lipidowy. W innym badaniu kobietom cierpiącym na zespół policystycznych jajników (polycystic ovary syndrome -PCOS) podawano cynamon i stwierdzono istotne zmniejszenie insulinooporności w porów-naniu z grupą otrzymującą placebo.…”
unclassified
“…Rozbieżności w badaniach nie pozwalają wyciągnąć jednoznacznych wniosków odnośnie do roli cynamonu w leczeniu cukrzycy typu 2. Konieczne są zatem dalsze badania w celu potwierdzenia lub wykluczenia korzystnego wpływu tej przyprawy na proces leczenia cukrzycy [47][48][49]51].…”
unclassified